COMPETENCY OF TVET INSTRUCTOR TOWARD TECHNICAL LESSON IN INSTITUT LATIHAN PERINDUSTRIAN (ILP) - Abdul Suki, Nabilah; Yunus, Faizal Amin Nur; Rahim, Mohd. Bekri; Masran, Saiful Hadi; Marian, Mohd Fairuz; Abd Baser, Jamil (Online Journal for TVET Practitioners, 2018)
There are many factors that cause poor production quality of TVET graduates and one of them is due to instructor's competency. Therefore, the purpose of this study is to identify the level of mastery for technical aspect, learning and methodology aspects, and humanity and social aspect of TVET instructor toward technical lesson in Institut Latihan Perindustrian (ILP). Besides that, the researchers want to identify the difference in the level of technical aspect, learning and methodology aspect as well as the humanity and social aspects of TVET Instructor competence based on the teaching experience in Institut Latihan Perindustrian. This study is a descriptive survey using a questionnaire as an instrument. Instruments for pilot study were analyzed using Winsteps software with Rasch Measurement Model approach. Total sample involve 126 TVET instructor from southern ILP that selected randomly. The data was analysed using descriptive and inferential statistic. The results show that the level of mastery of TVET Instructor from technical aspect (mean = 4.27), learning and metodology aspects (mean = 4.32) and humanity and social aspects (mean = 4, 10) are at high level. Inference analysis based on DGF (Differential Group Functioning) t-test does not differ in the level of mastery of technical aspects and humanity and social aspects but there is a difference in the level of mastery of learning and methodology aspect between middle-level instructors and experienced instructors.